Dilated Left Ventricular End-Diastolic Diameter Is a New Risk Factor of Acute Kidney Injury Following Coronary Angiography - Li, Qiang; Chen, Shiqun; Huang, Haozhang; Chen, Weihua; Liu, Liwei; Wang, Bo; Lai, Wenguang; Yi, Shixin; Ying, Ming; Tang, Ronghui; Huang, Zhidong; Deng, Jiayi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Purpose: Left ventricular end-diastolic diameter (LVEDD) is a common indicator in echocardiogram and dilated LVEDD was correlated with left ventricular insufficiency. However, it is uncertain whether dilated LVEDD is associated with increasing the risk of contrast-associated acute kidney injury (CA-AKI) in patients with coronary artery disease (CAD). Patients and methods: We enrolled 8,189 patients with CAD undergoing coronary angiography (CAG) between January 2007 and December 2018. Patients were divided into 2 groups according to the LVEDD length (normal LVEDD: men: LVEDD ≤56 mm, women: LVEDD ≤51 mm; dilated LVEDD: men: LVEDD >56 mm, women: LVEDD >51 mm). The endpoints are CA-AKI0350 and CA-AKI0525 (CA-AKI0350: an increase in the serum creatinine (Scr) level by >0.3 mg/dL or >50% within the first 48h after CAG; CA-AKI0525: an absolute Scr increase ≥ 0.5 mg/dL or a relative increase ≥ 25% within 72 hours after contrast medium exposure. In-hospital dialysis, 30-day mortality and 1-year mortality were contained as well. Univariate and multivariable logistic regressions were used to assess the association between LVEDD and CA-AKI. Results: Among 8,189 participants (males: 76.6%, mean age: 64.4±10.7 years), 1,603 (19.6%) presented with dilated LVEDD. In addition, the dilated LVEDD group indicated an elevation of CA-AKI0350 (12.4% vs. 6.2%, p<0.001) and CA-AKI0525(15.0% vs. 8.8%; p＜0.001) compared with the normal group. According to multivariable logistic analysis, dilated LVEDD was an independent predictor of CA-AKI0350 (adjusted odds ratio [aOR], 1.31; 95% CI, 1.06–1.61, p = 0.010) and CA-AKI0525 (aOR 1.32; 95% CI, 1.04–1.67; p = 0.020). Conclusions: In conclusion, these results demonstrated that the dilated LVEDD was a significant and independent predictor of CA-AKI following CAG in patients with CAD. Further verifications are needed to verification the association of LVEDD and CA-AKI.